Protective effect of traditional Chinese medicine on non-alcoholic fatty liver disease and liver cancer by targeting ferroptosis - Wu, Qiongbo; Chen, Zihao; Ding, Yi; Tang, Yunting; Cheng, Yawei (Frontiers in Nutrition, 2022)
Non-alcoholic fatty liver disease (NAFLD) is a chronic liver disease with high incidence and is closely related to metabolic syndrome. If not controlled, it may eventually become hepatocellular carcinoma (HCC). Ferroptosis, a non-apoptotic form of programmed cell death (PCD), is closely related to NAFLD and HCC, and the mechanisms of action involved are more complex. Some studies have demonstrated that many drugs inhibit ferroptosis and protect liver steatosis or carcinogenesis. The role of Traditional Chinese Medicine (TCM), especially herbs or herbal extracts, has received increasing attention. However, there are relatively few review articles on the regulation of NAFLD by TCM through ferroptosis pathway. Here, we summarize the TCM intervention mechanism and application affecting NAFLD/NAFLD-HCC via regulation of ferroptosis. This article focuses on the relationship between ferroptosis and NAFLD or NAFLD-HCC and the protective effect of TCM on both by targeting ferroptosis. It not only summarizes the mechanism of early prevention and treatment of NAFLD, but also provides reference ideas for the development of TCM for the treatment of metabolic diseases and liver diseases.